Synthesis and Properties of Thiophene and Aniline Copolymer Using Atmospheric Pressure Plasma Jets Copolymerization Technique - Jang, Hyo Jun (Polymers (Basel), 2020)
This paper investigates the properties of thiophene and aniline copolymer (TAC) films deposited by using atmospheric pressure plasma jets copolymerization technique relative to various blending ratios of aniline and thiophene monomer for synthesizing the donor–acceptor conjugated copolymers. Field emission scanning electron microscopy (FE-SEM) and atomic force microscopy are utilized to measure the surface morphology, roughness and film thickness of TAC films. Structural and chemical properties of TAC films are investigated by Fourier transforms-infrared spectroscopy (FT-IR), time of flight secondary ion mass spectrometry, and X-ray photoelectron spectroscopy. FE-SEM images show that the film thickness and nanoparticles size of the TAC films increase with an addition thiophene monomer in the aniline monomer. FE-SEM, FT-IR results show that TAC films are successfully synthesized on glass substrates in all cases. The iodine doped TAC film on the Si substrate with interdigitated electrodes shows the lowest electrical resistance at blending condition of thiophene of 25%.